2004
DOI: 10.1111/j.1365-2516.2004.01011.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA class II genotype and factor VIII inhibitors in mild haemophilia A patients with an Arg593 to Cys mutation

Abstract: We evaluated inhibitor formation in a group of patients with mild haemophilia A caused by an Arg593 to Cys mutation. A remarkably high cumulative inhibitor incidence of 14% over 22 years was observed. Three of 49 patients developed transient, low-titre inhibitors, which remained below 2.0 BU mL(-1). Four patients with an Arg593 to Cys mutation developed high-titre inhibitors (>5.0 BU mL(-1)). Three of these patients have been described previously. In this study, we characterized inhibitory antibodies in a four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 19 publications
3
24
1
Order By: Relevance
“…Inhibitor formation in mild haemophilia appears to be associated with relatively few high‐risk FVIII gene mutations in the A2 or C2 domains of FVIII, such as Arg593Cys, Arg2150His and Trp2229Cys (Hay, 1998; Bril et al , 2004).…”
Section: Haemophilia a And Neutralising Anti‐factor VIII Antibodiesmentioning
confidence: 99%
“…Inhibitor formation in mild haemophilia appears to be associated with relatively few high‐risk FVIII gene mutations in the A2 or C2 domains of FVIII, such as Arg593Cys, Arg2150His and Trp2229Cys (Hay, 1998; Bril et al , 2004).…”
Section: Haemophilia a And Neutralising Anti‐factor VIII Antibodiesmentioning
confidence: 99%
“…Moreover, the associationbetween HLA class II alleles and the FVIII inhibitorsin Thai hemophilia patients was further investigated inthis study, as recent studies have indicated that inhibitorformation depends upon an adequate T-cell responseby major histocompatibility complex class II moleculesto FVIII resulting from the presentation of FVIII proteinantigen to T-cell receptors [18-21]. It was reported that inmild hemophilia A patients with inhibitor the frequencyof DRB1*01 and DQB1*05 was slightly higher than thecontrols (but not significantly) [25]. A comparison of thefrequency data for DRB1*15/16 in hemophilia A patientswith FVIII inhibitor reported in other studies showed thatDRB1*15 and DRB1*16 were high-risk alleles for inhibitorformation in patients with congenital hemophilia Aand acquired hemophilia A, respectively [8-10].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some specific mutations seem associated with particular high risk for inhibitor development. An Arg593 to Cys mutation in the A2 domain of FVIII was associated with a cumulative inhibitor incidence of 14% after FVIII replacement over a period of 20 years (7/49 patients from 12 families) [16]. In the HAMSTeRS database, this mutation is associated with an inhibitor in 16.2% (6/37) of reported patients.…”
Section: Genetic Predisposition To Inhibitor Development In Patients mentioning
confidence: 99%